An Enhanced Half-Quasi-Z-Source Inverter for Wind Energy Conversion System with D-PMSG. (2nd July 2021) - Zhang, Yang; Cheng, Zhun; Chen, Qing; Li, Qingmei
Abstract : To solve the problem of the traditional quasi- Z -source inverters with low voltage gain, an enhanced half-quasi- Z -source inverter (E-HQZSI) is proposed and applied to direct-drive permanent-magnet wind power generation systems in this paper. The expression of the boosting factor is deduced, which shows that E-HQZSI has higher voltage gain compared with the QZSI and HQZSI. However, the higher voltage gain of the E-HQZSI will lead to the large distortion of the generator stator current necessarily. In this paper, a periodic shoot-through duty ratio control scheme is proposed to reduce the stator current harmonics for E-HQZSI. According to the change rule of the single-phase stator current, the shoot-through duty ratio is compromised to make that the three-phase stator currents are as close as possible to the sine wave. Finally, the correctness of the theoretical analysis is verified by simulation and experiment.